2005
DOI: 10.2174/157018005774717334
|View full text |Cite
|
Sign up to set email alerts
|

Szeged Index - Applications for Drug Modeling&#

Abstract: In this review we describe various applications of Szeged (Sz) index for modeling physicochemical properties as well as physiological activities of organic compounds acting as drugs or possess pharmacological activity.Keywords: Szeged index, physicochemical properties, biological activity, drug design, QSPR, QSAR, QSTR, multiple regression analysis. # On the eve of 70 th birthday of both Prof. Padmakar V. Khadikar and his wife Mrs. Kusum Khadikar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 53 publications
0
34
0
2
Order By: Relevance
“…10,16,17 Here we propose a novel version of the edge-Szeged index and its properties are discussed for several classes of (molecular) graphs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,16,17 Here we propose a novel version of the edge-Szeged index and its properties are discussed for several classes of (molecular) graphs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Szeged index has immediately been recognized as interesting and useful molecular descriptor, many contributions appeared to report its mathematical properties (e.g., References 2-9) and various applications to modeling the physicochemical properties and physiological activites of organic compounds. Khadikar et al 10 succinctly summarized the applications of the Szeged index in the quantitative structure-property-activity-toxicity modeling. In that paper the authors also stated that the total number of publications on the Szeged index and its variants up to the time of preparation of the paper is about 120 and among them more than 60 are reporting various applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These generalizations of Wiener index coincide for acyclic molecules (trees) but are quite different from each other for most cycle-containing structures. In structure-property research, Wiener index and its generalizations have found applications in a variety of fields, such as boiling points of alkanes [15], conformational switching in RNA structures [19], molecular cyclicity [16], drug modeling [20], and network bipartivity [21].…”
Section: Introductionmentioning
confidence: 99%
“…The Szeged index is a graph invariant that has been extensively studied, see, e.g., [2,[5][6][7]9,12,16,17].…”
Section: Introductionmentioning
confidence: 99%